Pengaruh Model Problem Based Learning(PBL) Integrasi ChatGPT terhadap Kemampuan Berpikir Kreatif Mahasiswa PAI UIN Mataram - Mauzifa Mauzifa; Baehaqi Baehaqi (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the application of the Problem-Based Learning (PBL) model integrated with ChatGPT media in the teaching of Contemporary Fiqh courses, specifically the material